FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KECEMASAN PASIEN YANG DIRAWAT DI RUANG ICU/ICCU RS HUSADA JAKARTA - Dameria Saragih; Yulia Suparmi (KOSALA : Jurnal Ilmu Kesehatan, 2017)
Critical care unit is a treatment unit with high risk of death of patient. Patients of ICUHusada Hospital approximately 4-5 patients who have full awareness (compos mentis)and ICCU patients about 5-6 patients compos mentis or compos mentis have a high riskof anxiety. This study was conducted to determine the factors that affect the level ofanxiety of patients treated in ICU / ICCU Husada Hospital. This research use crosssectional design. The sample of the study was 25 people, taken with saturated samplingmethod, because the population number is relatively small. The results of statisticalanalysis show that 60% of ICU and ICCU patients experience anxiety. There was asignificant relationship between sexes on anxiety level (p = 0.031), there was a significantcorrelation between length of care to anxiety level (p = 0.007), there was significantcorrelation between patient experience treated to anxiety level (p = 0.014) There is asignificant relationship between ICU and ICCU tools on the level of anxiety, there is asignificant relationship between ICU and ICCU tools on anxiety level (p = 0.002). There isa significant correlation between knowledge level and patient's anxiety level (p = 0.014).Conclusion: patient anxiety in ICU / ICCU influenced by many factors so that clearinformation from health officer is needed. Advanced research is required with larger andmore focused sample quantities.Keywords: intensive care unit, intensive critical care unit, anxiety, patients